Blood Urea Nitrogen to Creatinine ratio in Differentiation of Upper and Lower Gastrointestinal Bleedings; a Diagnostic Accuracy Study - Seyyed Mahdi Zia Ziabari; Siamak Rimaz; Afshin Shafaghi; Maryam Shakiba; Zahra Pourkazemi; Elnaz Karimzadeh; Melika Amoukhteh (Archives of Academic Emergency Medicine, 2019)
Introduction: Finding easily accessible and non-invasive methods for differentiating various sources of gastrointestinal (GI) bleeding before performing endoscopy and colonoscopy is of great interest. The present study was designed with the aim of evaluating the screening performance characteristics of blood urea nitrogen (BUN) to Creatinine (Cr) ratio in this regard.